2023
DOI: 10.47191/jefms/v6-i3-07
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Empowering Leadership on Organizational Commitment in The Police Institution: A Systematic Literature Review

Abstract: Multiple environmental pressures are exerting pressure on the police institution, and police officers must work hard to tailor their services to the needs of the community. This study was a systematic literature review aiming to investigate the impact of empowering leadership on organizational commitment in the police institution using Vos Viewer application. A total of ten journals published between 2018 and 2023 was reviewed thoroughly. The findings confirm that the empowering leadership has an effect on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 20 publications
3
2
0
Order By: Relevance
“…The results of this research are in line with the study findings of Dong et al, which revealed that police leadership was able to influence organizational commitment positively and significantly [3]. It is also in line with that of (Mohd & Nisa Mohd Arshad, Ardi, P Drahen, Taufiq et al, Azis [26,7,4].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results of this research are in line with the study findings of Dong et al, which revealed that police leadership was able to influence organizational commitment positively and significantly [3]. It is also in line with that of (Mohd & Nisa Mohd Arshad, Ardi, P Drahen, Taufiq et al, Azis [26,7,4].…”
Section: Discussionsupporting
confidence: 90%
“…This finding is in line with previously conducted research, such as that conducted by Dong et al, in which, they emphasized that effective leadership influenced police performance, especially if there was strong commitment among them [3]. In this regard, Ardi & P. Drahen, highlighted the importance of empowering leadership to enhance employee's compatibility with police agencies [7].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The results of this research are in line with the study findings of Dong et al, (2019), which revealed that police leadership was able to influence organizational commitment positively and significantly. It is also in line with that of (Mohd & Nisa Mohd Arshad, 2019;Ardi & P. Drahen, 2023;Taufiq et al, 2023;Azis., 2020).…”
Section: Discussionsupporting
confidence: 89%
“…Dong et al, (2019) conducted a study that effective leadership and strong commitment are potential to encourage increased individual performance in the police work environment. Ardi & P. Drahen, (2023) conducted a study that leaders who practiced empowering leadership increased employee compatibility with the organization, thereby increasing organizational commitment. The leadership is greatly related to the organizational effectiveness of the police institution.…”
Section: The Influence Of the National Police Leadership On The Polic...mentioning
confidence: 99%